Application of Password Services in an SMS Platform in Medical Record Copying. (June 2014) - Lin, Lin; Sun, Beibei
Abstract: Since medical records play an irreplaceable role in many fields, the medical record copying is particularly important. The contents of a medical record are confidential, so it cannot be copied without identity check; some patients and agents cannot copy the medical record because they may forget to take the valid identity documents. This article refers to the password service concept in service industries, and by applying the password services, the patients can set up service passwords for the medical records through the short message service (SMS) platform, so that in the ordinary application check, if the agents do not carry the valid identity documents of patients, the workers in the medical record room can prompt the agents to enter the known service passwords into the medical record management system, and the workers check the passwords with the service passwords pre-stored in the server of the hospital. If the agents enter the correct password, the identity check is successful. The purpose is to provide a new method of application for the patients and agents, so as to provide the patients and agents with people-oriented services and improve medical service quality.